The association between diabetes and mortality in young adults presenting with myocardial infarction. (14th October 2021) - Gyurjian, K; Chiu, S; Hammershaimb, B; Nadadur, M; Phan, P; Shen, Y J; Lin, B; Lee, M S
Abstract: Background: The incidence of diabetes mellitus and coronary artery disease continue to rise and collectively comprise two of the most prevalent and costly diseases worldwide. The goal of this study is to report the prognosis of young patients with diabetes presented with acute myocardial infarction (AMI). Methods: This is a retrospective observational cohort study that included consecutive patients aged 18–45 years who underwent cardiac catheterization for AMI between 2006 and 2016 in an integrated healthcare system in Southern California. The prognosis of patients with diabetes were compared to those without diabetes. Results: A total of 1, 560 patients (average age 40.2±5.3 years, 25.6% female) presenting with AMI were included. Of these 272 (17.4%) had diabetes. Diabetics were older (41.1±4.4 vs 40.0±5.4 years), more likely to be female (32.4% vs 24.1%, p=0.006), Hispanic (51.5% vs 40.5%, p<0.001), have a higher body mass index (BMI) (33.6±7.1 vs 31.2±6.8kg/m 2, p<0.001), have hypertension (HTN) (67.6% vs 23.8%, p<0.001), hyperlipidemia (HLD) (78.3% vs 24.1%, p<0.001), peripheral vascular disease (9.9% vs 1.9%, p<0.001), chronic kidney disease (CKD) (23.2% vs 2.7%, p<0.001), hypothyroidism (7% vs 4%, p=0.034), and prior strokes (4.4% vs 2.2%, p=0.034). On multivariate analysis accounting for other cardiovascular risk factors, the association remained significant (OR 1.82, 95% CI 1.04–3.19, p=0.036). At a median follow-up of 5.8 years (interquartile range 3.7–8.7 years), diabetes was independently associated with increased all-cause mortality (Hazard ratio [HR] 3.10, 95% CI 1.68–5.69, p<0.001) when adjusting for age, sex, race, BMI, HTN, HLD, CKD, hypothyroidism, prior stroke, and ACS etiology. In a propensity score matched cohort, diabetes remained significantly associated with all-cause mortality (HR 5.29, 95% CI 2.34–12.02, p<0.001). Conclusion: Diabetes is an independent predictor of increased mortality in young adults <45 years old presenting with AMI. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): KAISER PERMANENTE LOS ANGELES MEDICAL CENTER